PENGARUH GREEN INTELLECTUAL CAPITAL INDEX DAN PENGUNGKAPAN KEBERLANJUTAN TERHADAP KINERJA KEUANGAN DAN NON KEUANGAN PERUSAHAAN DENGAN TRANSPARANSI SEBAGAI VARIABEL MODERASI - Megawati Chandra; Yvonne Augustine (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
The purpose of this study was to examine green intellectual capital and sustainability disclosure in affecting financial and non financial firm performance with transparency as moderating variable in manufacture companies listed in Indonesia Stock Exchange. This research used 188 to 213 listed manufacture companies in Indonesia Stock Exchange, selected using purposive sampling method in period 2015 to 2017.The result of the analysis indicated that green intellectual capital index had positive influence on financial firm performance and transparency could moderating positive influence sustainability disclosure to financial firm performance (ROA) and non financial firm performance. While, sustainability disclosure had no influence on financial and non financial firm performance, transparency couldn’t moderating positive influence green intellectual capital index on financial and non financial firm performance, and transparency couldn’t moderating positive influence sustainability disclosure on financial firm performance (ROE).